Metamorfosis Faksionalisme Internal Partai Golkar di Maluku Utara pada PILKADA 2007 - MISRINA, MISRINA (Universitas Muhammadiyah Yogyakarta, 2010)
This research describes the dynamics of internal faction of Golkar party when the North MalukuGovernor election was held in 2007-2008. It can be observed during the process preelection tothe post-election. This research uses the qualitative method The data are collected by conductingthe documentation, observation, and interview. The result of this research shows, that thefactionalisms occurred in the Golkar party in the election of North Maluku governor caused twofactors, the pragmatism of supreme members of Golkar partyand the patron-client. The factioncharacteristic of Golkar party based on the faction fragmentation shows that there are twofactions (bipolar), which are the faction supporting Thaib and the faction supporting Gafur.